2013
DOI: 10.1002/lary.24009
|View full text |Cite
|
Sign up to set email alerts
|

Retropharyngeal lymph node dissection in oropharyngeal cancer treated with transoral robotic surgery

Abstract: In patients with tonsil cancer the risk of retropharyngeal metastases is negligible in the presence of clinically T1-2, N0-N2a disease and negative CT and PET-CT. We estimate that 40% of patients meet these criteria and may safely forego treatment of the retropharyngeal nodes. Approximately 10% of patients will have positive imaging and we recommend retropharyngeal node dissection at the time of surgery to treat macroscopic disease. In the remaining patients at risk for retropharyngeal node involvement, adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…The confirmation of tumor in retropharyngeal node metastasis that are FDG-avid on CT/PET has been performed in a small series of patients treated at the Mayo clinic. 18 All patients who had FDG-avid nodes on CT/PET had histologic confirmation of their metastasis, but they also found patients with no radiographic evidence of retropharyngeal adenopathy had micrometastasis in these lymph nodes on surgical sampling. These “occult N0” patients present a therapeutic dilemma as patients treated with surgery alone without retropharyngeal lymph node dissection may harbor microscopic disease that goes untreated.…”
Section: Discussionmentioning
confidence: 99%
“…The confirmation of tumor in retropharyngeal node metastasis that are FDG-avid on CT/PET has been performed in a small series of patients treated at the Mayo clinic. 18 All patients who had FDG-avid nodes on CT/PET had histologic confirmation of their metastasis, but they also found patients with no radiographic evidence of retropharyngeal adenopathy had micrometastasis in these lymph nodes on surgical sampling. These “occult N0” patients present a therapeutic dilemma as patients treated with surgery alone without retropharyngeal lymph node dissection may harbor microscopic disease that goes untreated.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs most commonly in tumors of the tonsil and lateral pharyngeal wall and seldom in tumors of the base of tongue . Few studies of the diagnostic accuracy of the various imaging modalities for the detection of RPLN metastasis have been conducted in which pathologic confirmation was available . Morrissey et al demonstrated 50% sensitivity and 70% specificity of CT to correctly identify metastasis in patients when compared to RPLND specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from Okumura et al indicated that MRI may be superior to CT in its ability to accurately assess RPLN, reporting a sensitivity of 83% for CT and 100% for MRI, and specificity of 100% when combining both CT and MRI. Moore et al placed the specificity and PPV of PET/CT at 100% and NPV at 92.6%. Subgroup analysis revealed that preoperative PET/CT studies failed to detect metastatic retropharyngeal disease in 2 of 7 cases (28.6%) with pathologically confirmed RPLN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…If desired, an angled view can also be obtained through a beveled endoscopic camera. These all can be very helpful in identifying and preserving adjacent neurovascular structures of the retropharyngeal and parapharyngeal spaces while maximizing and the adequacy of resection [12,13,20,21]. The ease of use of the articulating robot instrument arms coupled with the 3-dimensional optics of the camera gives the surgical robot advantages over the use of an endoscope (that has a 2 dimensional view) and long transoral non-articulating instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision of isolated retropharyngeal lymph node metastases from WDTC has been well described via trans-cervical, trans-mandibular, and trans-oral approaches, including endoscopic-assisted trans-oral resection [5][6][7][8][9][10][11]. Trans-oral robotic surgery (TORS) has been described for excision of metastatic retropharyngeal lymph nodes of oropharyngeal carcinoma and of parapharyngeal space tumors, but never for an isolated retropharyngeal metastasis from WDTC [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%